Analysis of the Influence of Financial Literacy and Digital Financial Inclusion on the Use of QRIS Among MSMEs - Maharani, Pingkan Ayu; Ajeng Kartika Galuh (Contemporary Studies in Economic, Finance and Banking, 2026)
The digital transformation of payment systems has encouraged Micro, Small, and Medium Enterprises (MSMEs) to begin implementing cashless payment technologies such as the Quick Response Code Indonesian Standard (QRIS). However, increased use of QRIS has not been fully accompanied by adequate levels of financial literacy and understanding of digital financial inclusion, resulting in suboptimal utilization. This study aims to analyze the influence of financial literacy and digital financial inclusion on the decision to use QRIS among MSMEs in Malang City. The study employs a quantitative approach using purposive sampling of 393 MSME owners who use QRIS. Data analysis was conducted using multiple linear regression with the help of SPSS. The results indicate that financial literacy and digital financial inclusion have a positive and significant effect on the decision to use QRIS, both partially and simultaneously. These findings reinforce the importance of improving financial literacy and expanding digital financial inclusion to promote the optimal use of QRIS among MSMEs.